PENGARUH PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS XII DI SMKN I BATAM - Ary Prasetyo; Sukarni Sukarni (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
ABSTRACTThis study aims the study of Parents attention to the learning achievement of Islamic Religious Education grade XII students at SMKN 1 Batam. The research method used in this study uses quantitative research methods. The population is all students of Islamic religion class XII at SMK 1 Batam. While the sample selection uses simple random sampling technique, 100 students out of 452 students who are Islamic students of class XII at SMKN 1 Batam. The instrument used in this study used a questionnaire containing closed questions. The data analysis technique used structural equation modeling (SEM) analysis with AMOS 24. The conclusion in this study was that the attention of parents (X) had a positive and significant direct effect on learning achievement (Y) of religious education for class XII students at SMKN 1 Batam by 5.7 %